FINANCIAL LITERACY AND INVESTMENT DECISIONS IN ISLAMIC FINANCIAL PRODUCTS - Nova Andriani; Poppy Camenia Jamil; Sinta Yulyanti (Jurnal Apresiasi Ekonomi, 2023)
This study aims to analyze Financial Literacy and Investment Decisions on Islamic Financial Products in Riau. The research method used is descriptive method and quantitative and qualitative analysis. The data collection technique uses a questionnaire that has been tested for its validity and rehabilitation. The research subjects were 154 respondents using purposive probability sampling technique and 25 interviewees. Meanwhile, the data analysis technique used is a simple linear regression equation, the management uses SPSS version 26 and Nvivo 12. Based on the results of the hypothesis testing it is known that financial literacy simultaneously has a significant effect on investment decisions on financial products in Riau Province.